Terahertz measurements of the Photoactive Protein Bacteriorhodopsin mutant D96N: M and P states - Chen, C.-Y.; Knab, J. R.; Cerne, J.; Hillebrecht, J. R.; Birge, R. R.; Markelz, A. G. (Mater. Res. Soc. Symp., 2004)
We use terahertz (THz) spectroscopy as a biomaterials characterization tool. Previously we have shown a strong contrast between the THz dielectric response for wild type (WT) and D96N mutant of bacteriorhodopsin. In those studies we observed a large increase in the THz absorbance of WT with excitation to thermally captured photo-intermediates whereas no such increase in absorbance was observed for the mutant D96N. These results suggest that the THz response is sensitive to structural changes and relative flexibility of biomolecules. However the photo-intermediate populations of the WT and D96N samples were not equivalent in those measurements. While the WT samples had relaxed (bR), M and P state intermediates present, the D96N samples had only bR and M states. Here we present terahertz absorbance measurements of D96N as a function of M and P state populations at room temperature. The THz response is constant for intermediate states populations up to 23% M state and up to 30% P state. These results verify that there is a fundamental difference in the conformational dynamics as measured by THz dielectric response for a single residue mutation.